Landmarks upon landmarks: The equator, geodesic monuments, and the Museo Inti-Ñan - Capello, Ernesto (2019)
In the Lulumbamba Valley, 20 kilometers from Quito, there is an obelisk celebrating the equator. This article presents a summary of the ties between the Andean equator and geodesic science, ties that resulted in the construction of an original monument in 1936 and a subsequent vibrant tourist economy. Secondly, it presents an oral history narrated by the director of an alternative equatorial museum, Fabián Vera, whose family has been linked with equatorial tourism since the 1950s. This oral history demonstrates the conflictive nature of an imaginary landmark, such as the equator, as well as the possibilities of homegrown tourism.